Healthy adults maximum oxygen uptake prediction from a six minute walking test (Faculty of Medicine Universitas Indonesia, 2011)
Background: A parameter is needed in medical activities or services to determine functional capacity. This study is aimed to produce functional capacity parameter for Indonesian adult as maximum O2. Methods: This study used 123 Indonesian healthy adult subjects (58 males and 65 females) with a sedentary lifestyle, using a cross-sectional method. Results: Designed by using the followings: distance, body height, body weight, sex, age, maximum heart rate of six minute walking test and lung capacity (FEV and FVC), the study revealed a good correlation (except body weight) with maximum O2. Three new formulas were proposed, which consisted of eight, six, and five variable respectively. Test of the new formula gave result of maximum O2 that is relevant to the golden standard maximum O2 using Cosmed® C-Pex. Conclusion: The Nury formula is the appropriate predictor of maximum oxygen uptake for healthy Indonesians adult as it is designed using Indonesian subjects (Mongoloid) compared to the Cahalin's formula (Caucasian). TheÂNury formula which consists of five variables is more applicable because it does not require any measurement tools neither specific competency. (Med J Indones 2011;20:195-200)